PENGARUH PROPORSI BAYAM DENGAN TEPUNG TERIGU TERHADAP KADAR ZAT BESI, SIFAT FISIK DAN SIFAT ORGANOLEPIK MIE BASAH - nur hidayati (Universitas Muhammadiyah Semarang, 2011)
This study aims to determine the effect of spinach on the noodles to Fe, physical and organoleptics properties. As Statistically analysis known significantly on the effect of adding spinach for Fe content, ie the addition of spinach by 10%, 20%, and 30%. However, there was not significantly on the physical properties of yield, rehydration and elasticity. Organoleptic testing showed the flavor and color of not significant. While the flavour is no difference in the effect of the addition of spinach occurred in 20%, 10% and 0% (control). Similarly, no effect of the difference in texture occurs on the addition of spinach, 20%, 30% and 0% (control). To increase the value of iron on wet noodles can be added spinach 20% and blanching the spinach to reduce unpleasant flavour.